2016
DOI: 10.3389/fpls.2016.00361
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Ethylene Signaling Induced by Endophytic Fungus Gilmaniella sp. AL12 Mediating Sesquiterpenoids Biosynthesis in Atractylodes lancea

Abstract: Ethylene, the first known gaseous phytohormone, is involved in plant growth, development as well as responses to environmental signals. However, limited information is available on the role of ethylene in endophytic fungi induced secondary metabolites biosynthesis. Atractylodes lancea is a traditional Chinese herb, and its quality depends on the main active compounds sesquiterpenoids. This work showed that the endophytic fungus Gilmaniella sp. AL12 induced ethylene production in Atractylodes lancea. Pre-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The signaling molecule solution (200 lL) was sprayed on plantlets and was allowed to flow from leaf surfaces to the roots. The chemicals and their dosages used here were selected based on previous studies, which showed that these compounds could efficiently suppress signaling molecule accumulation induced by bacterial inoculation but did not destroy normal plant ROS and hormone homeostasis Dai 2012, 2013;Ren et al 2014;Wang et al 2015a;Yuan et al 2016). Moreover, the inhibitors had no significant effects on bacterial colonization in planta, which ruled out the possibility that the suppression of essential oil accumulation was the result of reduced bacterial colonization (Fig.…”
Section: Chemicals and Treatmentsmentioning
confidence: 98%
See 3 more Smart Citations
“…The signaling molecule solution (200 lL) was sprayed on plantlets and was allowed to flow from leaf surfaces to the roots. The chemicals and their dosages used here were selected based on previous studies, which showed that these compounds could efficiently suppress signaling molecule accumulation induced by bacterial inoculation but did not destroy normal plant ROS and hormone homeostasis Dai 2012, 2013;Ren et al 2014;Wang et al 2015a;Yuan et al 2016). Moreover, the inhibitors had no significant effects on bacterial colonization in planta, which ruled out the possibility that the suppression of essential oil accumulation was the result of reduced bacterial colonization (Fig.…”
Section: Chemicals and Treatmentsmentioning
confidence: 98%
“…Inhibitors were sprayed on plant leaves until dripping wet and a 1-day infiltration period was allowed before bacterial inoculation or application of signaling molecules (Wang et al 2011(Wang et al , 2015bDai 2012, 2013;Ren et al 2014;Yuan et al 2016). Inhibitors remaining on the leaves were washed by the addition of the bacterial suspension and allowed to flow to the plant roots.…”
Section: Chemicals and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, plant defensive responses are aroused by perceiving fungal endophytes (Camehl et al, 2010;Yuan et al, 2019). Then, the activated signalling elements, such as reactive oxygen species and phytohormones, trigger the downstream synthetic pathways of secondary metabolites in planta (Yuan et al, 2016b;Zhai et al, 2017). These bioactive secondary metabolites can regulate the growth of fungal endophytes, which help symbiotic interactions to be maintained (Liu and Reinscheid, 2004;Schulz and Boyle, 2005).…”
Section: Introductionmentioning
confidence: 99%